Joseon's royal heritage 500 years of splendor - Koehler, Robert; Kim Eugene; Mouat, Colin A.; So-young, Min (Seoul Korea Foundation Seoul Selection, 2011)
Examines the three areas of Joseon cultural heritage: Seoul's royal palaces, the Joseon royal tombs, and the Annals of the Joseon dynasty.
"The content of this series is based on the material published in Koreana, the Korea Foundation's full-color quarterly featuring in-depth coverage of various aspects of Korea's cultural themes"--cover flap
Includes bibliographic reference (page 121).
Keywords: Architecture -- Korea; Palaces -- Korea; Korea -- Civilization -- 1392-1910.; Korea -- Kings and rulers -- Tombs